ANALYSIS RATIO FINANCE COMPANY PT MAYORA BEAUTIFUL TBK PERIOD 2020-2024 - Tahara Alsura; Lisa Aulia; Aiyuni Maulia; Uswatun Hasanah; Herman Fithra (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the financial performance of PT Mayora Indah Tbk based on financial ratio analysis. during period 2020–2024. Method study Which used is method descriptive quantitative using secondary data in the form of the company's annual financial reports. The analysis was conducted using liquidity, solvency, profitability, activity, and market ratios to assess the company's ability to meet financial obligations, generate profits, manage assets, and create value for investors. The research results show that PT Mayora Indah Tbk The company's financial performance remains relatively stable and is trending upwards after experiencing pressure in 2021. Liquidity and solvency ratios are at safe levels, demonstrating the company's ability to maintain financial stability. Profitability ratios improved significantly through 2023, though a correction occurred in 2024, but remained in the good category. Ratio activity show that management receivables walk efficient, although optimization asset utilization Still need improved. Temporary That, ratio market show perception investors Which positive to Company performance and prospects. Overall, the analysis shows that PT Mayora Indah Tbk has a healthy financial condition and good prospects to support future business sustainability